2012
DOI: 10.1088/0004-637x/752/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Solar Neutrino Physics: Sensitivity to Light Dark Matter Particles

Abstract: Neutrinos are produced in several neutrino nuclear reactions of the proton-proton chain and carbon-nitrogen-oxygen cycle that take place at different radii of the Sun's core. Hence, measurements of solar neutrino fluxes provide a precise determination of the local temperature. The accumulation of non-annihilating light dark matter particles (with masses between 5 GeV and 16 GeV) in the Sun produces a change in the local solar structure, namely, a decrease in the central temperature of a few percent. This varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…In particular, some of these papers have helped to set important constraints on the parameters of symmetric and asymmetric DM. Both the Sun, by means of helioseismogy (Lopes & Silk 2010b;) and solar neutrinos (Lopes & Silk 2010a, 2012a, as well as neutron stars (Kouvaris 2012;Kouvaris & Tinyakov 2011;Kouvaris 2008), are among the most useful stellar objects to constraining the properties of DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, some of these papers have helped to set important constraints on the parameters of symmetric and asymmetric DM. Both the Sun, by means of helioseismogy (Lopes & Silk 2010b;) and solar neutrinos (Lopes & Silk 2010a, 2012a, as well as neutron stars (Kouvaris 2012;Kouvaris & Tinyakov 2011;Kouvaris 2008), are among the most useful stellar objects to constraining the properties of DM.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we study the impact of light DM particles in the evolution of low-and intermediate-mass stars. In particular, we choose to focus our study on a class of particles that have properties in common with recent hints of direct detection of DM candidates, but also belong to a theoretical class of DM particles, known as asymmetric χχ-DM particles (Lopes & Silk 2012a). These particles, like WIMPs, are neutral, cold, massive particles that interact with baryons through a mechanism identical to weak interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical computation of the impact of dark matter in the evolution of the Sun and stars has progressed considerably in the last two decades [20,24,25], however, there are still a few caveats that must be addressed [17].…”
Section: The Dark Matter Inside the Sun And Starsmentioning
confidence: 99%
“…As a consequence the spin-independent scattering cross-section of the DM-target Baryon increases from 10 −40 cm 2 to 10 −37 cm 2 . Lopes and Silk [20] have shown that 8 B neutrino fluxes can reject the lower masses and higher values of scattering cross section. Further future 8 B neutrino flux measurements could lead to much better constraints (cf.…”
Section: Dark Matter Constraints From Sun and Starsmentioning
confidence: 99%
“…1). This phenomena has been studied in the case of the Sun, where the observations of solar neutrinos and helioseismology have been used to constrain the properties of DM [25][26][27].…”
Section: Impact Of Dark Matter On Starsmentioning
confidence: 99%